Продовження досліджень у м. Рівне - Прищепа, Б.А.; Чекурков, В.С.; Ткач, В.В. (Археологічні дослідження в Україні, 2010)
Results of excavations in 2008 and 2009 in Rivne at Korolenko Square are presented. At the areas allotted for construction, the Early Slavonic finds, Christian burials of the 12th and 13th centuries, cultural layers and objects of the Lithuanian-Polish epoch of the 14th—18th c. were discovered.